Deprescription in Advanced Cancer Patients Referred to Palliative Care. (2nd July 2016) - Oliveira, Liliana; Ferreira, Marta Oliveira; Rola, Alexandre; Magalhães, Miguel; Ferraz Gonçalves, José
ABSTRACT: In palliative care, drugs are considered futile if they do not have a short-term benefit in symptom control or quality of life. The authors examined pharmacotherapy prescribed for patients referred to palliative care to identify futile drugs. This was a retrospective analysis of patients referred over 6 months, focusing on the prescription of gastric protectants, antidiabetic agents, bisphosphonates, anticoagulants, antidementia drugs, statins, and antihypertensive agents. The sample consisted of 448 patients. Gastric protectants were prescribed futilely in 50% of cases (125/248), statins in 97% (69/71), antihypertensive agents in 27% (42/155), antidiabetic drugs in 1% (1/70), bisphosphonates in 27% (4/15), and antidementia drugs in 100% (9/9). This study reveals that many patients with advanced cancer continue to be treated with inappropriate drugs and points to the need for medical training in palliative care, drawing attention to the need for therapeutic review at each medical visit.